Ruthenium‐based complex dyes for dye‐sensitized solar cells. Issue 8 (19th June 2022) - Wu, Chun‐Guey
Abstract: Dye‐sensitized solar cell (DSC) has been a promising new‐generation photovoltaic technique. Sensitizer is one of the most important parameters that determine the photovoltaic performance of a DSC. This review article shows the step‐by‐step procedure of how to design high photovoltaic performance ruthenium‐based complex dyes for DSC. The strategy includes the extension of the conjugated length of the anchoring and ancillary ligands as well as using multidentated ligand and strong sigma donor to red‐shift to λ max of the metal‐to‐ligand charge transfer band and increase molar absorption coefficient, fine‐tune the functionality of the ligand to enhance dye regeneration, and using non‐mono‐dentated ligand to improve the dye stability. The review focuses on basic chemistry rather than the photovoltaic performance comparison between the ruthenium dyes introduced in this article. Abstract : Various ruthenium complexes were designed and prepared to be used in Dye‐sensitized Solar Cells. The results domenstrate the diversity structure and photovoltaic properties of ruthenium based dyes.